Foundations of computer assisted process engineering analysis for sustainable development of South cathcment basin at Lake Balaton - Varga, Mónika; Balogh, Sándor; Csukás, Béla (Acta Scientiarum Socialium, 2013)
Foundations of computer assisted process engineering analysis for sustainable development of South cathcment basin at Lake Balaton Literature survey starts from the concept of Computational Sustainability that is moving from computer assisted study on isolated ecological problems toward supporting the solution of large scale, long term problems of mankind. Approaching to the actual objectives, it is shown that computer simulation based water assessment of catchment basins has been solving with many sophisticated tools since many decades. However these formerly developed tools are not prepared fully for the process model based evaluation and automatic development of the human built possible scenarios. Zoom-ing in our specific aims, it is illustrated that motivated first by the decreasing of eu-trophication, next by the optional water supply, many detailed and thorough investigations have been running for Lake Balaton and its catchment basin. Regardless many recent project activities still there is an obvious gap between natural science & engineering results and the solution of social conflicts. Suggested foundations of our planned engineering analysis are based on our â€˜Direct Computer Mapping’ simulation methodology, combined with our Multi-objective Genetic Algorithm for problem solving. The main principles are the followings: (i) The coherence of the model is given by the discretized dynamic network of water flows and storages; (ii) The completeness is solved by the complete and disjunct covering of the whole area by modeled patches, responsible for the typical parts of natural and human built environment, associated with typical partial interests; (ii) The complexity of the large scale and long term process will be managed by generating and evaluating detailed models only for one representative patch form each class, while the calculation and assessment of the similar patches is solved by simple multiplication rules; (iv) Automatic and impersonal development of scenarios is realized by a multi-objective evaluation feedback, supporting the computational analysis of the consensus and conflict between the interest.